Traditional Agro-forestry Systems of Sikkim with Special Reference to Large Cardamom-alder Relationship - Avasthe, R. K.; Singh, Matber; Srivastava, L. S. (Indian Forester, 2007)
Sikkim with a total geographic area of 7,096 km2 reveals wide variations in altitude from 300m to 8,586 m amsl and the climate changes from sub-tropical to alpine with increase in altitude. This region receives copious rainfall with annual rainfall ranging from 2,000 to 5,000 mm. Nearly 70 per cent land is under forest and related land use with predominance of agroforestry systems. The present study reveals that nine major agroforestry systems are in practice in the sub-tropical and mid-hill temperate zones. Only three agroforestry systems were observed in the temperate zone viz., agri-horticultural, horti-silvi-pastoral and livestock-based mixed farming whereas in the higher altitudes the climate reduced the agroforestry systems to one in each zone. Horti-pastoral-transhumance and livestock-based mixed farming (beyond timberline)-transhumance were recorded in the sub-alpine and alpine zones, respectively. Livestock was an integral component of all the systems. The largest agroforestry system (AFS) was large Cardamom (Amomum subulatum Roxb.) as an undergrowth occupying the middle tier in the three-tier forest constitution with Alder (Alnus nepalensis) as the dominant companion. The economics of these two systems revealed that the large cardamom AFS (Rs. 92,700/-) generated almost double the annual returns than the maize-potato cultivation Rs. 48,000/- per hectare when seven income options were compared.